Optimization and Quality Evaluation of Oats (Avena sativa) Flour Incorporated Paneer - Khatri, Sabin Bahadur; Khadka, Kiran; Gautam, Navin; Khadka, Nabin; Raut, Bicky (Himalayan Journal of Science and Technology, 2023)
Efforts were initiated to prepare a carbohydrate, calcium and fibre rich paneer by addition of oat flour (Avena sativa). Six samples’ formulations were prepare including control paneer, (100% milk curd). The different formulations of (oats flour: milk curd) in the ratio as: sample (1:99), sample (1.5:98.5), sample (2:98), sample (2.5:97.5) and sample (3:97) to access the quality and acceptability of paneer. The experiment was designed by central composite mixture design and the obtained data was analyzed statistically by Genstat Discovery Edition 3 (DE3), for Analysis of Variance (ANOVA) at 5% level of significance version 12.1. The oats flour and milk curd for the development of value-added product, and evaluate proximate and sensory characteristics of product. The sensory evaluation revealed sample (1:99) was found to be best by comparing sensory score of overall acceptance given by the panelists and functional components. Crude protein, crude fat, total ash and carbohydrate of control product were found to be 41.43%, 49.7%, 4.39% and 4.44% whereas for best product the results were 40.54%, 48.97%, 4.39% and 5.92% respectively. The calcium content of best paneer and control paneer were found to be 467.08 mg/100 g and 399.12 mg/100 g respectively. The fiber contents were zero and 0.156% in control and best product sample (1:99) respectively. Therefore, it was concluded that the incorporation of oats flour for the formulation of value-added paneer will be helpful for developing value-added dairy products for the developing countries.